ARGILAS MONTMORILONITAS NATURAIS E MODIFICADAS COM SURFACTANTES APLICADAS NA ADSORÇÃO DO AZUL DE METILENO E P-NITROFENOL EM SOLUÇÃO AQUOSA. - Santos, Andressa dos (2010)
Dyes and phenolic compounds are substances widely used in various industries such as textile, food, oil and others. These industries have found problems in removing these substances in wastewater mainly because the stability of their molecules. Many alternative adsorbents have been studied in the removal of dyes from aqueous solutions. This study investigated the efficiency of removal of the methylene blue dye (MB) and the p-nitrophenol (PNF) phenolic compound in ASAT and ASV raw and modified with the cationic surfactant CTAB. The effects of contact time and initial concentration of adsorbate on the adsorption were analyzed. The first one had no influence on adsorption and the second one was directly proportional to the amount adsorbed. The experimental data concerning the adsorption of MB on clay in nature was adjusted to the kinetic model of pseudo-second order model and the Langmuir isotherm. The maximum adsorption capacity was 288.18 mg gˉ¹ (ASAT) and 291.54 mg gˉ¹ (ASV) at 60°C. The thermodynamic parameters indicated an endothermic adsorption process, favorable and spontaneous. The experimental data on the adsorption of PNF in organoclay was adjusted to the model of pseudo second-order model and Freundlich isotherm. The adsorption capacity was observed and obtained at a concentration of 400 mg Lˉ¹, for ASAT/100CTC of 272.75 mg gˉ¹ and ASV/200CTC of 239.91 mg gˉ¹ at 25ºC. Thermodynamic parameters indicated that the adsorption was a reversible process, exothermic and non-spontaneous. Factors affecting the adsorption were studied such as pH, ionic strength, adsorbent dosage and temperature. The insertion of CTAB on clay and the adsorption adsorbate were confirmed on the characterization of the material by infrared spectroscopy, Raman spectroscopy, thermogravimetric analysis, X-ray diffraction and SEM / EDS.